2010
DOI: 10.1002/sce.20418
|View full text |Cite
|
Sign up to set email alerts
|

Science teachers' views of science and religion vs. the Islamic perspective: Conflicting or compatible?

Abstract: This paper reports a study that explores Egyptian science teachers' views on religion and science within the context of Islam. It also highlights an ontological and epistemological consideration of these views, particularly the ways through which Egyptian Muslim teachers understand such a relationship with reference to the Qur'anic/Islamic attitude toward science and knowledge. The study built upon Barbour's categorization scheme to guide the data collection and analysis and to guide the interpretation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(38 citation statements)
references
References 50 publications
1
30
0
7
Order By: Relevance
“…After all, as Mansour (2011) explained, 'the Prophet's sayings take a pragmatic and utilitarian view of knowledge, which can be sought outside Islam if necessity demands it' (p. 303). The author agrees with this interpretation of the Hadith suggested by Mansour (2011) and Golshani (2007) and, in particular, with the view that science and mathematics are compatible with traditional Islamic beliefs.…”
Section: Recent Ksa Mathematics and Science Educational Initiativessupporting
confidence: 86%
“…After all, as Mansour (2011) explained, 'the Prophet's sayings take a pragmatic and utilitarian view of knowledge, which can be sought outside Islam if necessity demands it' (p. 303). The author agrees with this interpretation of the Hadith suggested by Mansour (2011) and Golshani (2007) and, in particular, with the view that science and mathematics are compatible with traditional Islamic beliefs.…”
Section: Recent Ksa Mathematics and Science Educational Initiativessupporting
confidence: 86%
“…There is a range of primarily qualitative studies that have described different views regarding the science and religion issue. Many of these studies use Barbour's () typology of science and religion relationships to identify students’ or teachers’ views (e.g., Mansour, ; Taber et al., ). In our study, several attitude profiles match the conflict view ( P1 , P3 , P4 , and P7 ), whereas the more‐harmonious profiles ( P2 and P5 ) belong to dialogue, independence or integration.…”
Section: Discussionmentioning
confidence: 99%
“…Other inquiries revealed that Muslim teachers and students tend to use a combination of theological and biological explanations when making sense of evolution and other biology concepts because scientific and theological domains are often intertwined or diffused in their minds (Haidar 1999(Haidar , 2002Aroua et al 2009;Asghar et al 2009a). The tensions that arise between the secular values that come with modern science and teachers' theological frameworks may lead to outright rejection or modification of certain scientific ideas to seek harmony between Islam and science (Mansour 2008(Mansour , 2011. Notably, scientific evidence did not seem to influence the thinking of those who rejected or selectively accepted evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the Scientific Academies of several predominantly Muslim countries (e.g., Egypt, Indonesia, Iran, Pakistan) are signatory to a statement proclaiming that evolution is an 'evidence based fact' which has never been contradicted by scientific evidence (Inter-Academy Panel 2006). Mansour (2011) explicates the powerful role of Islam in shaping Muslim intellectual and broader publics' response to modern science. According to him, Islam in most contemporary Muslim communities is not just restricted to moral and spiritual beliefs like other religions.…”
Section: Islamic Perspectives On Biological Evolutionmentioning
confidence: 99%
See 1 more Smart Citation